Diagnosis of invasive fungal infections in haematological patients by combined use of galactomannan, 1, 3-β-D-glucan, Aspergillus PCR, multifungal DNA-microarray, and Aspergillus azole resistance PCRs in blood and bronchoalveolar lavage samples: results of a prospective multicentre study. (October 2016) - Boch, T.; Spiess, B.; Cornely, O.A.; Vehreschild, J.J.; Rath, P.M.; Steinmann, J.; Heinz, W.J.; Hahn, J.; Krause, S.W.; Kiehl, M.G.; Egerer, G.; Liebregts, T.; et al.
Abstract: High mortality rates of invasive fungal disease (IFD), especially invasive aspergillosis (IA), in immunocompromised haematological patients and current diagnostic limitations require improvement of detection of fungal pathogens by defining the optimal use of biomarkers and clinical samples. Concurrent bronchoalveolar lavage (BAL) and peripheral blood samples of 99 haematological patients with suspected IFD were investigated within a multicentre prospective study. Diagnostic performance of a galactomannan (GM) enzyme immune assay (EIA), a 1, 3-β-D-glucan assay (BDG), an Aspergillus PCR, and a multifungal DNA-microarray (Chip) alone or in combination were calculated. IFD were classified as proven ( n =3), probable ( n =34), possible ( n =33), and no IFD ( n =29) according to EORTC/MSG criteria. GM, PCR, and Chip showed superior diagnostic performance in BAL than in blood, whereas specificity of BDG in BAL was poor (48% (14/29)). The combination of GM (BAL) with BDG (blood) showed sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and DOR (diagnostic odds ratio) of 92% (34/37), 93% (27/29), 94%, 90%, and 153.0, respectively. Combining GM (BAL) with PCR (BAL) showed convincing diagnostic potential for diagnosing IA with sensitivity, specificity, PPV, NPV, and DOR of 85% (17/20), 97% (28/29), 94%, 90%, and 158.7. Addition of the DNA-microarray resulted in further detection of two mucormycetes infections. In 1 out of 15 Aspergillus DNA-positive samples a triazole resistance-mediating Cyp51A mutation was found. Combination of biomarkers is superior to their sole use in diagnosing IFD, particularly IA. Integrating blood and BAL samples into a diagnostic algorithm is an advantageous approach.